Air velocity behaviour at tropical urban plazas adjacent to tall buildings: a case study of Kuala Lumpur - Abdul Majid, Noor Hanita; Sapian, Abdul Razak (Malaysian Institute of Energy and Malaysia Energy Centre, 2000)
The paper presents the air velocity field experiments at three tropical urban plazas adjacent to tall buildings (PATB) in Kuala Lumpur. The built-up of Kuala Lumpur City especially the central business areas with its high density of tall structures, reduces the wind speed due to the friction effect. At the plazas adjacent to tall buildings, the air velocity varies accordingly to the geometry of the PATBs. The three different geometry of PATBs analysed in this paper are: plaza on the side of tall building, plaza surrounded by tall buildings and plaza underneath tall building. These typologies are three main PATBs available in Kuala Lumpur. Utilising the data from these study locations, the effect of the typologies on the air velocity measurements are studied. Wind flow at the PATB can contribute in lowering the temperature and humidity, thus making the PATBs more comfortable. This paper also discusses the air velocity data from the field measurement in comparison to the data from the Petaling Jaya Meteorological Service Station, which is also representative of the urban location. The comparison exercise is to reduce the differences due to the unique of different PATBs.